Implementation of a Clinical Pharmacy Training Program in Iraqi Teaching Hospitals : Review Article - Jawad I. Rasheed; Hassan M. Abbas (College of Pharmacy University of Baghdad, 2017)
Pharmaceutical care is a patient-centered, outcomes oriented practice that requires the pharmacist to work in concert with the patient and the patientâ€™s other healthcare providers to promote health, to prevent disease, and to assess, monitor, initiate, and modify medication use to assure that drug therapy regimens are safe and effective. In addition, the presence of clinical pharmacists has led to a higher quality of patient education and provision of complete detailed information for patients. In developed countries Pharm D has become the professional degree for practice of Pharmacy. The graduates will be enrolled in a pharmacy residency program; admission to the residency programs is available to Pharm D graduates of an accredited College of Pharmacy. The residency is also designed to prepare the residents to become Board Certified Specialists in their field.  In many developing countries three new pharmaceutical education programs have currently been established to serve the pharmaceutical care development. Firstly, a six-year curriculum leading to the doctor of pharmacy (Pharm. D) degree as the sole professional degree. Secondly, Pharmacy Residency and Fellowship Training Program have been developed to provide intensive training in pharmaceutical care practice to the pharmacists. Lastly, the continuing pharmaceutical education program (CPE) has been adopted to ensure the competency of all pharmacists to deliver the best knowledge and skills in pharmaceutical sciences in their specialties. In our opinion we lack for most of these programs, even the program of clinical pharmacy in ministry of health is not residency program and it is short and not subspecialized apart from being not recognized by academic institutes and references.  In conclusion, pharmacy profession has to change towards the more responsibility on patient care. New training program has to be adopted by medical education institutes to provide clinical pharmacists as a profession and to prepare board certified clinical pharmacists as specialists to cope with the advances in all medical fields. Key words: clinical pharmacy, board certification.